Pengembangan Media Komik Digital Materi Sel Terhadap Keterampilan Berpikir Kritis Siswa MAN 3 Medan - Alfitrah Boban Hartady; Rahmadina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop a digital comic learning media on cell topics and to analyze its validity, practicality, and effectiveness in improving students’ critical thinking skills at grade XI of MAN 3 Medan. The research employed a Research and Development (R&D) method using the 4D model, consisting of define, design, develop, and disseminate stages. The research instruments included validation sheets from material and media experts, teacher and student response questionnaires, as well as pretest and posttest assessments. The validation results showed that the digital comic media was categorized as highly valid, with a score of 93.9% from media experts and 87.8% from material experts. Practicality testing indicated a teacher response score of 87% and a student response score of 81.9%, both classified as very practical. The effectiveness analysis showed an increase in the average learning outcomes from 82.96% in the pretest to 89.26% in the posttest, with an N-Gain score of 0.31, which falls into the moderate category. This result was influenced by the high initial ability of the students. In conclusion, the developed digital comic media is valid, practical, and moderately effective in supporting the improvement of students’ critical thinking skills on cell material. Keywords: Digital Comic, Learning Media, Cell System, Critical Thinking, Biology